Absolute Quantification of Noncoding RNA by Microscale Thermophoresis. Issue 28 (2nd May 2019) - Jacob, Dominik; Thüring, Kathrin; Galliot, Aurellia; Marchand, Virginie; Galvanin, Adeline; Ciftci, Akif; Scharmann, Karin; Stock, Michael; Roignant, Jean‐Yves; Leidel, Sebastian A.; Motorin, Yuri; Schaffrath, Raffael; et al.
Abstract: Accurate quantification of the copy numbers of noncoding RNA has recently emerged as an urgent problem, with impact on fields such as RNA modification research, tissue differentiation, and others. Herein, we present a hybridization‐based approach that uses microscale thermophoresis (MST) as a very fast and highly precise readout to quantify, for example, single tRNA species with a turnaround time of about one hour. We developed MST to quantify the effect of tRNA toxins and of heat stress and RNA modification on single tRNA species. A comparative analysis also revealed significant differences to RNA‐Seq‐based quantification approaches, strongly suggesting a bias due to tRNA modifications in the latter. Further applications include the quantification of rRNA as well as of polyA levels in cellular RNA. Abstract : The absolute quantification of non‐coding and coding RNA was achieved by microscale thermophoresis in a process involving target RNA hybridization to a complementary fluorescently labeled DNA probe and monitoring of changes in thermophoretic mobility. This method can be applied for the accurate quantification of tRNAs, rRNAs, and polyA RNA pools.